Domestikasi Perempuan Salafi: Konstruksi Sosial Perempuan Salafi di Kota Metro Lampung - Khotijah Khotijah; Ahmad Madkur (Kafa`ah: Journal of Gender Studies, 2018)
In the midst of a current era where gender equality is increasingly echoed, there are salafi groups, especially for women, who try to obey the mainstream. In this way, they even tend to have cultivation of a new  way to counter the old culture. In the midst of a negative stigma towards the characteristic of their dress that tends to be closed and restricted by their husbands,  many salafi women are able to move forward and do not miss the non-Salafi women in general. This research attempt to reveal the concept of Islamic women social live according to Salafi doctrine in the middle plurality of Metro regency. The findings of this study conclude that the woman do not experience significant social interaction in social aspect. They can even others you as a woman in general. Associated domestication by husbands, they believe that it is basically not the husband's command but more on the shari'a they believe in